Adjustment of state owned and foreign-funded enterprises in China to economic reforms, 1980s - 2007: A logistic smooth transition regression (LSTR) approach - Joshua Aizenman; Nan Geng (University of California, Economics Department, 2009)
This paper applies a logistic smooth transition regression approach to the estimation of a homogenous aggregate value added production function of the State Owned (SOE) and Foreign-Funded Enterprises (FFE) in China, 1980s-2007. The transition associated with the economic reforms in China is estimated applying a curvilinear logistic function, where the speed and the timing of the transition are endogenously determined by the data. We find high but gradually declining markups in both SOEs and FFEs during the early stages of the adjustment, with SOEs having a much larger scale and market size than the FFEs. However, over the transition process, returns to scale in industrial SOEs dropped sharply. For both FFEs and SOEs the transition is slow, with a midpoint about 7 and 14 years, respectively. We find significant increase of TFP growth rate for both FFEs and SOEs, by 0.1436 and 0.1971, respectively.
Keywords: 330; Systemtransformation; Wirtschaftsreform; Unternehmenserfolg; Sozialistisches Unternehmen; Ausländische Tochtergesellschaft; China